PENGGUNAAN ALIH KODE DALAM KOMUNIKASI DI APLIKASI TIKTOK - Sadi Desmiati, Fitria; Yundi Fitrah; Rahmawati (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This research aims to describe the forms and contexts of code-switching in communication on TikTok. The method used is descriptive qualitative with observation, listening, note-taking, and documentation techniques applied to 11 accounts actively using language variations. A total of 14 code-switching data were found, consisting of 3 internal code-switching data and 11 external code-switching data. This phenomenon is used to tailor language to the audience, emphasize the message, create humor, and simultaneously showcase bilingual and multicultural identity. This finding confirms that code-switching on TikTok is not just a linguistic phenomenon, but also a digital communication strategy. This research is expected to enrich sociolinguistic studies and provide new insights into language dynamics on social media.